Constructivist Teaching and Analytical Literacy for Fostering Critical Thinking among Islamic Higher Education Students - Amrullah; Karolina, Asri; Langputeh, Sukree (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
This study explores the impact of constructivist teaching strategies and analytical literacy on students' critical thinking skills among Islamic higher education students. A quantitative approach with an experimental research design was used, where data were collected via a Likert-scale questionnaire measuring three variables: constructivist strategy, analytical literacy, and critical thinking. The sample comprised 60 students from the English Education Program at IAIN Curup, selected using total sampling from three classes during the even semester 2025. Multiple linear regression analysis revealed that both constructivist strategy and analytical literacy significantly influenced critical thinking, with a coefficient of determination (R²) of 0.538, indicating that these two variables could explain 53.8% of the variance in critical thinking. The F-test showed a significant joint effect (F = 33.142, p < 0.05), while the t-test indicated that analytical literacy had a stronger individual impact (t = 4.588, p < 0.05) compared to the constructivist strategy (t = 1.807, p = 0.076).